Mental Health Associated with the Teaching of Medicolegal Autopsy among Medical Students in Sikkim School of Medicine - Bhutia, Karma Mingur Diki; Debbarma, Sankha Subhra (Achievements and Challenges of Medicine and Medical Science Vol. 2, 2024)
Background: Contemplating the curriculum of an Indian Medical Undergraduate, the demonstration of autopsy is still considered to be the cornerstone of Forensic Medicine. A medicolegal autopsy has always been perceived negatively by the public either due to their religious beliefs or due to their preconceived notions or fear of handling dead bodies’ associated with laws. Considering these prejudices, a study was undertaken not only to assess the knowledge, attitude & perception of a medical undergraduate but also to understand the reflection of this societal stigma on a medical student. It was these reasons that led to the study of Mental Health Associated with the Teaching of Medicolegal Autopsy among Medical Students in Sikkim Manipal Institute of Medical Sciences, Sikkim Manipal University to specifically determine how knowledge, attitude & practice influence the mental health of medical students while learning medicolegal autopsy in forensic medicine. Materials and Methods: Descriptive cross-sectional and triangulation designs were used in the survey and interviews of 200 medical students pursuing medicine in SMIMS, Gangtok, Sikkim who participated voluntarily in the study wherein structured questionnaire in Google form was distributed through Google link validated through their electronic mail i.d. & registration number. Results: Out of 191 medical students, the number of students was predominantly females with a ratio of 1:1.30 (M: F). 87.96% of the students knew that the medicolegal autopsy is done for all sudden, suspicious & unexpected deaths, and 90.05% of students strongly affirmed that the medicolegal autopsy ascertains the cause of death. The spectrum of ease with which the students watched the autopsy was almost along the same wavelength, 27.75% of students were comfortable, 25.13% were uncomfortable, 17.80% were indifferent and 29.32% were not yet exposed (due to online teaching). The majority of students (93.72%) are interested in watching more postmortem examinations being done than dissecting themselves, fearing that the dead person being dissected may arise while in the process of dissecting the corpse. Conclusions: The attitude of the students was confident towards autopsy & awareness among the participants was found to be acceptable. However, there were still a lot of prejudices that needed to be addressed through open discussion, logical explanation & scientific declaration at regular intervals to remove fear & negate any rudimentary beliefs or ideologies associated with medicolegal autopsies in Forensic Medicine.